2019
DOI: 10.3390/ijms20246196
|View full text |Cite
|
Sign up to set email alerts
|

Health Functions and Related Molecular Mechanisms of Tea Components: An Update Review

Abstract: Tea is widely consumed all over the world. Generally, tea is divided into six categories: White, green, yellow, oolong, black, and dark teas, based on the fermentation degree. Tea contains abundant phytochemicals, such as polyphenols, pigments, polysaccharides, alkaloids, free amino acids, and saponins. However, the bioavailability of tea phytochemicals is relatively low. Thus, some novel technologies like nanotechnology have been developed to improve the bioavailability of tea bioactive components and consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
167
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 270 publications
(171 citation statements)
references
References 238 publications
(328 reference statements)
0
167
0
4
Order By: Relevance
“…Food-derived bioactive compounds are increasingly explored for their ameliorative effects against metabolic diseases. For example, our group and others have extensively examined the beneficial effects of rooibos tea, including its bioactive compounds such as aspalathin, as well as other pharmacological compounds with abundant antioxidant properties like berries, n-acetyl cysteine, and gallic acid against diverse metabolic disorders [16][17][18][75][76][77][78][79][80]. Consistently, an extensive literature has been reviewed on the impact of resveratrol in ameliorating metabolic disease-associated complications [20,66,67].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Food-derived bioactive compounds are increasingly explored for their ameliorative effects against metabolic diseases. For example, our group and others have extensively examined the beneficial effects of rooibos tea, including its bioactive compounds such as aspalathin, as well as other pharmacological compounds with abundant antioxidant properties like berries, n-acetyl cysteine, and gallic acid against diverse metabolic disorders [16][17][18][75][76][77][78][79][80]. Consistently, an extensive literature has been reviewed on the impact of resveratrol in ameliorating metabolic disease-associated complications [20,66,67].…”
Section: Discussionmentioning
confidence: 99%
“…All included animal studies in this systematic review met the minimum requirements for publication using the ARRIVE guidelines checklists with 20 questions. Briefly, the median score range of all included studies was 15 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) out of a possible score of 20. The introduction domain had a median score of 4 (4-4) out of the possible score of 4 (overall agreement 100%, kappa = 1) whilst the methods domain had a median score of 6 (2-9) out of a possible score of 9 (overall agreement 88.89%, kappa = 0.76).…”
Section: Risk Of Bias and Quality Of The Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…An early randomized trial of oral squamous cell carcinoma (OSCC) prevention showed reduction in dysplastic lesions by consuming a GT extract in capsules combined with direct application of 1 g GT extract to the lesion [ 23 ] but a later trial showed no statistically significant benefit of GT in capsules as shown in Table 2 [ 24 ]. Notably, GT polyphenols are typically consumed in capsules when tested in recent clinical trials on cancer prevention, unlike human epidemiological studies, which may contribute to results [ 24 , 25 , 26 ]. Conflicting findings have also been seen for GT consumption and incidence rates for a number of other cancers, with modestly lower rates of liver and prostate cancer of self-reported tea drinkers based on meta-analysis [ 27 , 28 , 29 , 30 ].…”
Section: Gt Inhibition Of Human Cancermentioning
confidence: 99%
“…Plant metabolism produces numerous secondary metabolites (phytochemicals) that are very specific to each plant family and do not participate directly in the growth and development of the plant and [1,2]. Phytochemicals are known to possess a wide range of properties including antioxidant, hypoglycaemic, anticholinesterase, hypolipidemic, antiviral, antibacterial, antifungal, anti-inflammatory and cytotoxic activities as comprehensively reviewed by Pinakin et al 2020 andTang et al 2019 [3,4]. Although plants are considered an important natural source for therapeutic applications with well-known ethnomedical uses in literature, yet they have been poorly investigated from the phytochemical point of view as exemplified by a recent review on the genus Tragopogon of Asteraceae family [5].…”
Section: Introductionmentioning
confidence: 99%